1998
DOI: 10.1111/j.1574-6941.1998.tb00487.x
|View full text |Cite
|
Sign up to set email alerts
|

Enumeration of amino acid fermenting bacteria in the human large intestine: effects of pH and starch on peptide metabolism and dissimilation of amino acids

Abstract: Proteins and trichloroacetic acid‐soluble peptides were present in high concentrations in human intestinal contents and faeces. Free amino acids were also detected in millimolar amounts in proximal and distal colon contents, with hydroxyproline, alanine, lysine and valine predominating, showing that a wide variety of organic N‐containing compounds was available for fermentation by intestinal bacteria. Measurements of products of dissimilatory amino acid metabolism (ammonia, branched chain fatty acids) demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
162
3
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 211 publications
(177 citation statements)
references
References 49 publications
11
162
3
1
Order By: Relevance
“…The genus Bacteroides displays a high flexibility to adapt to the nutritional conditions of the intestinal environment (Comstock and Coyne, 2003), being able to use dietary or host-derived glycans according to the nutrient availability (Sonnenburg et al, 2005). Bacteroides can also incorporate amino acids from outside (Smith and MacFarlane, 1998) which could be used to maintain cell structures and as an energy source.…”
Section: A Focus On the Genus Bacteroides And The Production Of Propimentioning
confidence: 99%
See 1 more Smart Citation
“…The genus Bacteroides displays a high flexibility to adapt to the nutritional conditions of the intestinal environment (Comstock and Coyne, 2003), being able to use dietary or host-derived glycans according to the nutrient availability (Sonnenburg et al, 2005). Bacteroides can also incorporate amino acids from outside (Smith and MacFarlane, 1998) which could be used to maintain cell structures and as an energy source.…”
Section: A Focus On the Genus Bacteroides And The Production Of Propimentioning
confidence: 99%
“…The pH in the caecum is about 5.7 but gradually increases to 6.7 in the rectum. Dietary fiber fermentation promotes a slight decrease of the luminal pH whereas high protein/amino acids fermentation, favored by low carbohydrate availability, causes slightly pH increases (Smith and MacFarlane, 1998). Interestingly, a recent study with mice demonstrated that diet-microbiome interactions are driven by the pattern of protein and carbohydrate intake (Holmes et al, 2017).…”
Section: Modulation Of the Intestinal Bacteroides By Dietary Carbon/nmentioning
confidence: 99%
“…Protein is an abundant substrate for bacterial growth in the human intestine, possibly more so than carbohydrate in the distal colon [1]. Some of the protein may be of dietary origin, but large intestinal fermentation probably depends more on endogenous sources, including mucus and host proteins and bacterial protein resulting from bacterial cell turnover.…”
Section: Introductionmentioning
confidence: 99%
“…Proteolytic species from the human colon have been well characterized [1,8,9], and some aspects of the metabolism of peptides are known [1,10]. Bacterial species able to grow on individual amino acids as N and energy source are fairly well understood [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation